A educação especial em escolas estaduais no município de Humaitá-AM : um olhar sobre as práticas educativas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Faced with the concern about how educational practices are being developed in Special Education, as a teaching modality, especially in the pandemic period and what support is available for the teacher, some guiding questions were formulated with the aim of analyzing these practices. In the discourses of researchers, teachers and in the discourse of the State, we sought to characterize the teaching process developed by educators in order to understand the subject produced by this set of practices. The approach of this study is archeogenealogical and the paths used were: the construction, analysis and questioning of the archive. The scenario is two state schools, here called Alpha and Omega, which centralize the care of ninety students with disabilities. Data collection considered the Foucauldian perspective proposed in the approach and used what it took to find the answer to your problem and understand its event. Therefore, a questionnaire was applied to two teachers who work in a regular classroom, three teachers who work in specialized educational services and, seeking to understand the effect of educational practice on the final subject, an interview was carried out with a public employee with disabilities who studied since childhood. and completed high school at Alfa school. The discursive formations arising from the analysis of the responses were organized by axes according to the disciplinary device and the doubts that arose during the study were clarified via instant messaging application with the consent of the participants. It was concluded that despite the authors claim that we move between the integrative and inclusive paradigm, the research showed that we are sliding in a circular way between the paradigms and most of the time we still remain in the segregating model. It also indicated that educational practices are timid despite the efforts of teachers of specialized educational services, thus showing that only a minority of regular teachers adopt an educational procedure that is close to the inclusive concept.
Special education in state schools in the municipality de Humaitá-AM: a look at educational practices
Keywords: CIENCIAS HUMANAS; Educação Especial; Arqueogenealogia; Foucault; Problematização; Ensino